Global DNA methylation changes in Cucurbitaceae inter-species grafting - Avramidou,Evangelia (2015)
Grafting has been used to improve yield, fruit quality and disease resistance in a range of tree and vegetable species. The molecular mechanisms underpinning grafting responses have only recently started to be delineated. One of those mechanisms involves long distance transfer of genetic material from rootstock to scion alluding to an epigenetic component to the grafting process. In the research presented herein we extended published work on heritable changes in the DNA methylation pattern of Solanaceae scion genomes, in Cucurbitaceae inter-species grafting. Specifically, we examined global DNA methylation changes in scions of cucumber, melon and watermelon heterografted onto pumpkin rootstocks using MSAP analysis. We observed a significant increase of global DNA methylation in cucumber and melon scions pointing to an epigenetic effect in Cucurbitaceae heterografting. Exploitation of differential epigenetic marking in different rootstock-scion combinations could lead to development of epi-molecular markers for generation and selection of superior quality grafted vegetables.